FACTORS AFFECTING THE PERFORMANCE OF USER GOODS ADMINISTRATOR/PROVIDER ADMINISTRATOR WITH LEADERS' COMMITMENT AS A MODERATING VARIABLE (EMPIRICAL STUDY IN THE RIAU ISLANDS PROVINCIAL GOVERNMENT) - Nelly Huzrin Hood; Indrayani; Muammar Khaddafi (PT. Radja Intercontinental Publishing, 2023)
This study aims to examine the factors that influence the performance of administrators of user goods/administrators of auxiliary user goods with leadership commitment as a moderating variable within the Riau Archipelago Provincial Government. Factors that influence include the following competency, compliance, and motivation. The population in this study were all administrators of user goods/administrators of auxiliary user goods in the Riau Archipelago Provincial Government with purposive population using a total of 188 respondents. From a population 188 respondents only 128 respondents answered the questionnaire via the google form.So the sample for this study was 128 respondents. Data Analysis used SPSS Version 25. In this study, several tests were carried out including validity and reability tests, multicollineariry tests, heteroscedasticity tests, normality tests, multiple linear regression analysis, t (partial) tests, simultaneous F tesrs, and tests of coefficient of determination.